Seismic hazard assessment in the Northern Aegean Sea (Greece) through discrete Semi-Markov modeling. - Pertsinidou, C. E.; Tsaklidis, G.; Papadimitriou, E. (Bulletin of the Geological Society of Greece, 2013)
Semi-Markov chains are used for studying the evolution of seismicity in the Northern Aegean Sea (Greece). Their main difference from the Markov chains is that they allow the sojourn times (i.e. the time between successive earthquakes), to follow any arbitrary distribution. It is assumed that the time series of earthquakes that occurred in Northern Aegean Sea form a discrete semi-Markov chain. The probability law of the sojourn times, is considered to be the geometric distribution or the discrete Weibull distribution. Firstly, the data are classified into two categories that is, state 1: Magnitude 6.5 -7 and state 2 Magnitude>7, and secondly into three categories , that is state 1: Magnitude 6.5-6.7, state 2: Magnitude 6.8-7.1 and state 3: Magnitude 7.2-7.4 . This methodology is followed in order to obtain more accurate results and find out whether there exists an impact of the different classification on the results. The parameters of the probability laws of the sojourn times are estimated and the semi-Markov kernels are evaluated for all the above cases . The semi-Markov kernels are compared and the conclusions are drawn relatively to future seismic hazard in the area under study.